2013
DOI: 10.3389/fnbeh.2013.00215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated adolescent stress and serotonin transporter gene partial knockout in mice on behaviors and brain structures relevant to major depression

Abstract: In humans, exposure to stress during development is associated with structural and functional alterations of the prefrontal cortex (PFC), amygdala (AMY), and hippocampus (HC) and their circuits of connectivity, and with an increased risk for developing major depressive disorder particularly in carriers of the short (s) variant of the serotonin transporter (5-HTT) gene-linked polymorphic region (5-HTTLPR). Although changes in these regions are found in carriers of the s allele and/or in depressed patients, evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 109 publications
1
11
1
Order By: Relevance
“…Ours is the first to accurately report MRI derived volumes of the BLA with excellent concordance to histology. A number of previous studies have attempted to derive amygdala volumes from MRI (Bouilleret et al, 2009;Kassem et al, 2013;Spinelli et al, 2013) using standard imaging methods. These studies reported amygdala volumes ranging from 56-100 mm 3 that are not consistent with those reported from anatomical studies (Chareyron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ours is the first to accurately report MRI derived volumes of the BLA with excellent concordance to histology. A number of previous studies have attempted to derive amygdala volumes from MRI (Bouilleret et al, 2009;Kassem et al, 2013;Spinelli et al, 2013) using standard imaging methods. These studies reported amygdala volumes ranging from 56-100 mm 3 that are not consistent with those reported from anatomical studies (Chareyron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The principal issue is insufficient anatomical boundaries from which to assess amygdala volumes (Delgado y Palacios et al, 2014). Even, increasing resolution by increasing imaging times in ex vivo brains has not resulted in reliable amygdala volumes (Spinelli et al, 2013). DTI has been used previously to enhance visualization of the human (Entis et al, 2012;Solodkin et al, 2013) and rodent brain (Zalsman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, overall, our results show that exercise clearly affects cognitive flexibility in SERT HET mice, on both the MWM and the spatial pattern separation touchscreen task. Further investigation of the effects of chronic voluntary exercise on the hypothalamic-pituitary-adrenal axis ("stress axis") of the SERT mutants would be interesting, especially since SERT HET mice exposed to repeated stress have shown impairments, relative to controls, in a probabilistic reversal learning task (Spinelli et al, 2013).…”
Section: Behaviourmentioning
confidence: 99%
“…In this current study, we examined whether the partial disruption of SERT from development was sufficient to alter the cellular and behavioural effects of voluntary exercise in adulthood. SERT heterozygous (HET) mice have been established as a relevant model of 5-HTTLPR S allele carriers and widely used to study G × E interactions both during development and in the adult brain (Carola et al, 2008;Kästner et al, 2015;Schraut et al, 2014;Spinelli et al, 2013). For instance, early life stress exposure causes SERT HET mice to display depressive-like behaviour (Carola et al, 2008), mirroring both the clinical findings (Caspi et al, 2003) and the phenotype of constitutive SERT homozygous knockout (KO) rodents (Kalueff, Olivier, Nonkes, & Homberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…With the more recent development of numerous rodent atlas automated image‐processing tools (Budin et al, ; Ma et al, ), rapid phenotyping of mouse models is also possible. As a result, DBM has now also been used in mouse models to examine autism (Horev et al, ; Steadman et al, ), fragile X syndrome (Ellegood et al, ), Huntington's disease (Carroll et al, ), Alzheimer's disease (Badhwar et al, ), and depression (Spinelli et al, ).…”
Section: Phenotyping Using Mri‐based Atlasesmentioning
confidence: 99%